Implementation of an Android Mobile Location-Based Service Application for General Auto Repair Shops - Ignacio, Aris E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The need of a location-based service more specifically as a mobile application sparked the interest of this paper to develop an Android Mobile Application using Location-based services. Yelp and Zomato are one of the few examples. The application created is specific to locating the nearest auto repair shops used via smartphones that detect the location of the user in order to perform the task. This application will not only benefit the customers in need for a nearby auto shop but as well as the providers of the service. The application was developed using Android Studio and was tested by using five (5) nearest auto shops around the vicinity. The results showed the directions getting to the shops as well as the type of services being provided to customers. An acceptability survey was conducted to validate the applicability of the mobile application. The survey was conducted using a controlled group consisting of the nearest auto shops and thirty (30) automobile enthusiasts. The survey presents an applicable and engaging application in assisting possible customers in case of emergency instances arise. Using the survey as basis, an enhancement of the application was completed. Finally, it was suggested that the application will reach its full potential once additional functions are implemented. Registration or Google verification of shop owners is key as it will add to the service provider directory to enable a broad listing.